Profil Literasi Matematika Peserta Didik Pada AKM Berdasarkan Gaya Belajar KOLB - Hufadz Iftitahul Jamili; Sumartono Sumartono; Lusiana Prastiwi (J-PiMat : Jurnal Pendidikan Matematika, 2026)
Mathematical literacy is one of the fundamental skills that students must possess to meet the challenges of the 21st century, particularly in solving contextual problems. This study aims to analyze the mathematical literacy skills of Phase F students in solving AKM questions as viewed through Kolb’s learning styles. This is a descriptive qualitative study conducted in the 11th-grade class at Dr. Soetomo High School in Surabaya. It consisted of four subjects selected using purposive sampling to represent each learning style. Data collection was conducted through the administration of the KLSI 3.1 learning style questionnaire, a mathematical literacy test, and interviews. The research results generally indicate that students with high mathematical literacy skills were able to meet all indicators, such as converging, assimilating, and accommodating learners. Diverging learners (DL) tended to feel bored, resulting in a lack of focus and difficulties in performing calculations. Converging learners (SC) are able to analyze information and apply mathematical concepts systematically. Assimilating learners (SAs) are able to analyze information logically, provide structured answers, and interpret results effectively. Accommodating learners (SAc) are able to analyze information and tend to solve problems based on prior learning experiences. The findings of this study indicate that differences in learning styles influence how students analyze and solve mathematical problems, which can serve as a consideration for teachers in designing instruction.Keyword: Mathematical Literacy, AKM, Kolb Learning Styles